„W ogóle jestem niechętny dźwiękom”. Muzyka w filmie Tatarak Andrzeja Wajdy - Al-Araj, Anna (Przestrzenie Teorii, 2017)
The aim of this article is to interpret the musical layer of Andrzej Wajda’s 2009 movie Tatarak (Sweet Rush), based on the novel by Jarosław Iwaszkiewicz. In the first part, the author attempts to depict the complex relationship between the literary and film works of these two artists and emphasizes three main motifs used by both of them: love and death, water and women’s themes. Next, Wajda’s attitude to music is analyzed. He treats sounds as an element of everyday life and, as is typical for our times, he is aware of the “dissolution” of musical works. In the next part, the author articulates the main problems of Sweet Rush, drawing attention to both Iwaszkiewicz’s novel and Wajda’s movie. The director’s adaptation, which is full of intermedia references, revolves around the theme of death and seems to underestimate the sexual aspect of Iwaszkiewicz’s work. Finally, Pawel Mykietyn’s soundtrack to Sweet Rush is interpreted. The composer used one of his earlier Shakespeare’s Sonnets (2000), which plays the role of a leitmotif, to illustrate the most enigmatic, inexplicable scenes from Wajda’s movie. Thanks to its discrete, sparing and “austere” nature, Mykietyn’s music made the artistic composition of Sweet Rush more balanced and revealed the suggestiveness of this work.